Case Report: Significant Response to the Combination of Lenvatinib and Immune Checkpoint Inhibitor in a Patient With Heavily Pretreated Metastatic Triple Negative Breast Cancer - Lee, Jin Sun; Yost, Susan E.; Yuan, Yuan (Frontiers in Oncology, 2021)
Background Triple negative breast cancer (TNBC) has poor prognosis without targetable mutations. The combination of lenvatinib and pembrolizumab has shown clinical activity in different types of solid tumors. Case Presentation We report a case of one patient with metastatic TNBC who has been heavily pretreated. The patient had been treated with multiple lines (≥ 8 lines) of chemotherapy without durable clinical responses. Her tumor regressed significantly under the combination of lenvatinib and immune checkpoint inhibitor, and remains stable for 10 months. Conclusions The combination of lenvatinib and immune checkpoint inhibitor may have significant clinical activity in selective patients with heavily pretreated metastatic TNBC.